Alcohol in Europe: epidemiology, policies and sustainable health targets to fill the gaps of prevention - Emanuele Scafato; Claudia Gandin; Silvia Ghirini; Alice Maton (Nutrimentum et Curae)
According to the World Health Organization (WHO), the harmful use of alcohol stands as a primary risk factor affecting the global population’s health. In 2016, 5.5% of all deaths in the 30 countries of the European Union (EU) were attributed to alcohol. In the past year, 62.3% of adults in the WHO European Region consumed alcoholic beverages at least once, contributing to nearly one million deaths annually, averaging around 2,500 deaths per day.